1987
DOI: 10.2190/v5q3-g0tk-xmwx-g0q0
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Prevention Program for Children: A Review

Abstract: Since smoking is recognized as one of the most significant health hazards, researchers have directed a lot of energy in combating this health hazard, in particular in the prevention of children taking up smoking. Health education has been advocated as the most effective preventive approach to this problem, however, the findings from this approach are equivocal. This article 1) reviews the literature regarding factors associated with children's initiation into smoking, and 2) examines the efficacy of health edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…This suggestion is not new and is consistent with the literature. Although research such as this has not yet been carried out with children with GRC, it has been completed with children with alcohol-related (Kraus et al 1994) and cigarette-related (Oei & Fae, 1987 ;Oei & Baldwin, 1992) cognitions. Any future prevention or intervention among children needs to take into account the continuing effects of family influences.…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion is not new and is consistent with the literature. Although research such as this has not yet been carried out with children with GRC, it has been completed with children with alcohol-related (Kraus et al 1994) and cigarette-related (Oei & Fae, 1987 ;Oei & Baldwin, 1992) cognitions. Any future prevention or intervention among children needs to take into account the continuing effects of family influences.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the early non-smoking prevention programmes were designed to provide people with information about the disadvantages of smoking (Flay, 1985;Oei & Fea, 1987). While it has been argued that smokers need to be presented with arguments against smoking, it has also been suggested that the vast majority of smokers are by now well aware of the dangers of tobacco use (Tuakli, Smith, & Heaton, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the emphasis has been on school-based programmes [23][24][25]. Programmes designed to teach young people the skills to resist social pressure and use of peer led groups have arguably had the most success [26]. The involvement of the broader community in student programmes has also resulted in some success [27].…”
Section: Cessation Among School Youthmentioning
confidence: 99%